(untitled) (Journal of the College of Basic Education, 2022)
School bullying, whether physically, verbally, social or sexual, is one of the problems that have negative effects on the bullying victim or the victim of bullying or on the school environment or on the society as a whole, and because the identification of school bullying among middle school students contributes to the creation of an educational environment that ensures the development of students of all abilities, abilities and preparations, they have resorted to choosing this topic. The current research aimed at :-identifying school bullying in middle school students. To identify the differences in school bullying among middle school students according to the gender variable (male-female). The current research sample was limited to (450) students of middle school students selected in a random class way and the researcher prepared the research tool, which is the study measure of bullying consisting of (48) paragraphs and extracted for this measure the seikometric characteristics of honesty, stability and discrimination of paragraphs and after applying the measure showed the following results: - 1- That middle school students have a school bullying. 2- There are significant differences between males and females in school bullying and for the benefit of males. The researcher has made many recommendations and